A Structural Model of Employee Behavioral Dynamics in Enterprise Social Media - Huang, Yan; Singh, Param Vir; Ghose, Anindya (Management Science, 2015)
We develop and estimate a dynamic structural framework to analyze the social-media content creation and consumption behavior of employees within an enterprise. We focus, in particular, on employees’ blogging behavior. The model incorporates two key features that are ubiquitous in blogging forums: users face (1) a trade-off between blog posting and blog reading; and (2) a trade-off between work-related and leisure-related content. We apply the model to a unique data set comprising the complete details of the blog posting and reading behavior of employees over a 15-month period at a Fortune 1000 IT services and consulting firm. Despite getting a higher utility from work-related blogging, employees nevertheless publish a significant number of leisure posts. This is partially because the creation of leisure posts has a significant positive spillover effect on the readership of work posts. Counterfactual experiments demonstrate that leisure-related blogging has positive spillovers for work-related blogging, and hence a policy of abolishing leisure-related content creation can inadvertently have adverse consequences on work-related content creation in an enterprise setting. When organizations restrict leisure blogging, the sharing of online work-related knowledge decreases and this in turn can also reduce employee performance rating. Overall, blogging within enterprises by employees during their work day can have positive long-term benefits for organizations. This paper was accepted by Lorin Hitt, information systems.